Deficiencies in health-related quality-of-life assessment and reporting: a systematic review of oncology randomized phase III trials published between 2012 and 2016. (10th October 2018) - Marandino, L; La Salvia, A; Sonetto, C; De Luca, E; Pignataro, D; Zichi, C; Di Stefano, R F; Ghisoni, E; Lombardi, P; Mariniello, A; Reale, M L; Trevisi, E; et al.
Abstract: Quality of life (QoL) is a relevant end point and a topic of growing interest by both scientific community and regulatory authorities. Our aim was to review QoL prevalence as an end point in cancer phase III trials published in major journals and to evaluate QoL reporting deficiencies in terms of under-reporting and delay of publication. All issues published between 2012 and 2016 by 11 major journals were hand-searched for primary publications of phase III trials in adult patients with solid tumors. Information about end points was derived from paper and study protocol, when available. Secondary QoL publications were searched in PubMed. In total, 446 publications were eligible. In 210 (47.1%), QoL was not included among end points. QoL was not an end point in 40.1% of trials in the advanced/metastatic setting, 39.7% of profit trials and 53.6% of non-profit trials. Out of 231 primary publications of trials with QoL as secondary or exploratory end point, QoL results were available in 143 (61.9%). QoL results were absent in 37.6% of publications in the advanced/metastatic setting, in 37.1% of profit trials and 39.3% of non-profit trials. Proportion of trials not including QoL as end point or with missing QoL results was relevant in all tumor types and for all treatment types. Overall, 70 secondary QoL publications were found: for trials without QoL results in the primary publication, probability of secondary publication was 12.5%, 30.9% and 40.3% at 1, 2 and 3 years, respectively. Proportion of trials not reporting QoL results was similar in trials with positive results (36.5%) and with negative results (39.4%), but the probability of secondary publication was higher in positive trials. QoL is not included among end points in a relevant proportion of recently published phase III trials in solid tumors. In addition, QoL results are subject to significant under-reporting and delay in publication.